Acidity tuning of montmorillonite K10 by impregnation with dodecatungstophosphoric acid and hydroxyalkylation of phenol - Garade, Ajit C.; Kshirsagar, V. S.; Mane, R. B.; Ghalwadkar, Ajay A.; Joshi, U. D.; Rode, C. V. (Applied Clay Science, 2010)
Acidity tuning of montmorillonite K10 (mont K10) was achieved by impregnating with dodecatungstophosphoric acid (DTP). The effect on the hydroxyalkylation of phenol was studied at 353 K with phenol to formaldehyde molar ratio of 5. The nature and strength of acid sites were determined by NH(3)-TPD measurement while the distribution of Brensted and Lewis acid sites expressed as B/L ratio, was determined by pyridine IR technique. Among various loadings of DTP (5-60%) studied for the hydroxyalkylation of phenol, 20% DTP/mont K10 showed the highest catalyst activity (90% selectivity to bisphenol F with 28% conversion of phenol). Both total concentration of acid sites and the distribution of acid sites in a high temperature region were required for the high bisphenol F selectivity. Our catalyst (20% DTP/Mont K10) could be recycled three times. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Acidity tuning; Dodecatungstophosphoric acid/Montmorillonite K10; Hydroxyalkylation; Impregnation; Temperature programmed desorption